Crystal structure of dimethyl 1-acetyl-1,2-dihydro-2,3-quinolinedicarboxylate, C15H15NO5 - Ramazani A.; Dolatyari L.; Kazemizadeh A. R.; Souldozi A. (Zeitschrift für Kristallographie - New Crystal Structures, 2004)
C15H15NO5, triclinic, P1̅ (no. 2), a = 7.366(1) Å, b = 8.884(2) Å, c = 11.242(2) Å, α = 68.640(4)°, β = 81.328(4)°, γ = 85.050(4)°, V = 676.9 Å3, Z = 2, Rgt(F) = 0.064, wRref(F2) = 0.151, T = 120 K.